PERSEPSI HARGA DAN NIAT BELI ULANG PADA PASAR BISNIS-KE-BISNIS: STUDI PADA PELANGGAN INDUSTRI PRODUSEN PVC STABILIZER DI INDONESIA - Alfarizy Bagus Kartika Witjaksono; Agus Hasan Pura Anggawidjaja (Parahyangan Management Science and Practices Student Review, 2025)
Retaining industrial customers is a persistent challenge for manufacturers that compete against lower-priced imports, yet most evidence on how price perception shapes repurchase intention comes from consumer (B2C) settings. This study examines the effect of price perception on repurchase intention among the industrial customers of a PVC stabilizer manufacturer in Indonesia, the only domestic producer in its category. Using an explanatory quantitative design, data were gathered through a census (saturated sampling) of all 31 customer firms, with purchasing decision-makers as respondents. Data were analysed through descriptive statistics, classical assumption tests, and simple linear regression using SPSS 27. Price perception has a positive and statistically significant effect on repurchase intention (b = 0.342; t = 9.686; p < 0.001) and explains 76.4% of its variance. Firms that judged the price as fair relative to the value and quality received reported high repurchase intention, whereas small-volume, price-sensitive firms that perceived the price as unfavourable against cheaper imports were the ones that discontinued purchasing. The findings extend the price-perception–repurchase link to a B2B, sole-domestic-supplier context and suggest that volume-based pricing and clearer value communication can strengthen retention.